Bioconvection Flow in the Presence of Casson Nanoparticles on a Stretching/Shrinking Vertical Sheet with Chemical Reaction - B. Arun; M. Deivanayaki; Selvakumar Kuppusamy Vaithilingam (Journal of Chemistry)
A Casson nanoparticle is used in this study to investigate the effects of toxic reactions, temperatures, and concentrations on convective heat transfer flow across a stretching/shrinking vertical sheet. The goal is to convert the control linear partial differential equations (PDEs) into an ordinary differential equations (ODEs) set and analyses them statistically using the Bvp4c technique in MATLAB software. It is necessary to look how various variables, such as the Casson nanofluid measurement, the chemical change constants and Prandtl numbers, the concentration-thermal-buoyancy ratio, the microorganism-to-thermal-buoyancy rate of return, the Lewis number, and other bioconvection-related parameters (such as the variation in micro-organism concentration and the buoyancy parameter), affect each other. The numerical results of the velocity, temperature, concentration, and bioconvection flow profiles are displayed.